Lumpang Batu dan Batu Dakon di Kabupaten Lebak Banten: Indikasi Bercocok Tanam Masa Lampau: Mortar And Dakon Stones in Lebak, Banten: Indications For The Human Plantation of The Past - Nurul Laili (JURNAL PANALUNGTIK, 2021)
Lebak Regency is an area in the southern part of Banten Province which is fertile and dominated by agricultural land. The condition of Lebak in the past based on archaeological remains, especially megalithic remains, shows traces of farming. The traces of the megalithic remains in the form of mortars and dakon stones were obtained at three sites, namely the Gunung Anakan site, the Parigi Lebakbinong site, and the Pasir Nangka site. The problem raised in this paper is what is the function of the mortar stone and dakon stone for supporting communities in Lebak Banten. Knowledge of the function of mortar and dakon stone will be able to reconstruct the role of mortar and dakon stone in the past related to farming. This paper uses descriptive analytical methods and inductive reasoning with a material culture approach. The existence of mortar and dakon stone indicates subsistence based on agriculture or farming.